Sports Cardiology - Edouard P; 2; Blanco D; Steffen K; Nielsen RO; 6; Verhagen E; Ruffault A; 9 (Deutsche Zeitschrift für Sportmedizin)
Problem: Low response rate to weekly self-reported questionnaires used to obtain athlete health-related and risk exposure data and low compliance with intervention have been reported. We thus aimed to investigate if time to 1) non-response to a weekly questionnaire and 2) non-compliance with an intervention is different among French athletics athletes with different characteristics.Methods: We performed a secondary analysis of data from the PREVATHLE randomized controlled trial including 840 female and male competitive athletics athletes followed over 39-weeks. Using univariate Cox proportional hazards regression models, we analyzed the association between athletes baseline characteristics and the following outcomes: time to failing to (1) respond to a weekly questionnaire and (2) complete a prescribed intervention.Results: Most athletes failed to complete all questionnaires over the 39 weeks (n=672, 80%), athletes in the intervention group, female athletes, younger athletes, athletes performing explosive disciplines, and athletes with higher non-specific sport training failed sooner. Nearly all athletes in the intervention group failed to comply with the intervention (n=443; 98.7%), and the rates were similar amongst athletes with different characteristics. Conclusions: This study shows that novel ways have to be found in order to improve both 1) athletes self-reported responses to weekly questionnaires on health-related and risk exposure data and 2) athletes compliance with an injury risk reduction program. Education and/or digital solutions might be potential opportunities.Key Words: Sports Injury Prevention, Prevention Strategies, Self-Reported Questionnaire, Track and Field